Universal health coverage: The case of China - William Hsiao; Mingqiang Li; Shufang Zhang (United Nations Research Institute for Social Development (UNRISD), 2015)
In less than a decade, China transformed its inadequate, unjust health care system in order to provide basic universal health coverage (UHC) for its people. What forces made it possible for China to achieve this? What kind of transformation took place? What are the impacts of these policy changes? What can we learn from China? Moreover, while China has achieved UHC in basic health services, this does not mean that everyone has equal access to the same quality of affordable health care. This paper, which uses a theory of political economy to analyse Chinas policy changes and accomplishments, consists of four main sections. Section I reviews the historical development of the Chinese health care system from the 1950s through the 1990s, tracing the serious consequences of the policy shift in the 1980s when the health care system and health care delivery became privately financed and commercialized. Section II analyses the political economy factors that drove and shaped the reform of the Chinese health system, focusing on the politics, institutions and actors that synergistically led to the establishment of UHC in 2009. In this section, we modified slightly John Kingdons theory and used it to examine four main streams of forces to explain how Chinas reform came about. (1) The problem stream shows how Chinese political leaders recognized a serious, widespread public discontent regarding health and then diagnosed the root causes of these health problems. (2) The policy stream examines how major stakeholders in the health sector proposed, and heatedly debated, different policy options based on their vested interests and ideologies. (3) The financial stream highlights how Chinas health policy was driven by fiscal constraints. (4) The politics stream analyses the political factors that influenced the agenda setting and policy formulation of UHC in authoritarian China, albeit with limited political transparency. The paper tracks these streams with historical evidence to conclude that the policy changes for UHC in China were established by the convergence of these four streams. Section III presents the policy outcomes - the current financing structure of the UHC (i.e., the three different insurance schemes, their benefit packages, and key companion programmes to assure the supply of basic services). Based on quantitative evidence, we summarize the impacts of Chinas UHC in terms of equitable access to health care, quality and affordability of health care, health outcomes, and financial risk protection from high and/or catastrophic medical expenses. Although Chinas UHC was a great achievement, stark disparities remain between urban and rural residents in China, along with high health expenditure inflation rates arising from inefficiency and waste in the health care system. In section IV, we discuss the remaining challenges for Chinas health care system and comment on the potential lessons of the Chinese experience for other nations.
Keywords: 330